2021
DOI: 10.1186/s12871-020-01222-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of laryngeal mask airway-supreme and endotracheal tube use with respect to airway protection in patients undergoing septoplasty: a randomized, single-blind, controlled clinical trial

Abstract: Background There are doubts among anesthesiologists on the use of the Laryngeal Mask Airway (LMA) in nasal surgeries because of concerns about the occurrence of blood leakages to the airway. We hypothesized that the use of LMA-Supreme (LMA-S) in nasal surgery is comparable with endotracheal tube (ETT) according to airway protection against blood leakage through the fiberoptic bronchoscopy, oropharyngeal leakage pressure (OLP), heart rate (HR), mean arterial pressure (MAP), and postoperative adv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Studies on Ambu® AuraGain™ LMA generally found that it was similar or superior to ETT in terms of hemodynamic data [5,12,15]. The analysis of heart rates in our study showed higher values in the ETT group at intubation.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Studies on Ambu® AuraGain™ LMA generally found that it was similar or superior to ETT in terms of hemodynamic data [5,12,15]. The analysis of heart rates in our study showed higher values in the ETT group at intubation.…”
Section: Discussionsupporting
confidence: 54%
“…The groups had similar characteristics in terms of demographic data (Table 1). The insertion times were 13 (5) seconds in the LMA group and 50 (15) seconds in the ETT group. Three patients in the ETT group developed nausea, and 1 patient in the LMA group developed a cough.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This study was performed on 80 patients undergoing thoracic and abdominal surgery under general anesthesia who were referred to Hazrat Fatemeh Hospital affiliated to Iran University of Medical Sciences in Tehran during March 2020-September 2020 (Figure 1). The sample size was calculated to be 40 for each group using a web-based formula considering α = 0.05, 1-β = 0.9, and effect size = 0.71 (12). The inclusion criteria were ASA 1 or 2 based on the physical status classification system and being in the age range of 25 -60 years.…”
Section: Methodsmentioning
confidence: 99%
“…The advantages of LMA compared to tracheal intubation are no tracheal injury during tube installation and removal, less airway stimulation, less invasion of the airway tissue, easier installation, and efficient establishment (6)(7)(8)(9). Therefore, in adults, it is recommended to use LMA as a substitute for tracheal intubation, especially in patients with a history of intubation, the possibility of difficult intubation diagnosed by an anesthesiologist, and patients whose intubation has failed and venti-lation can be performed with a mask (10)(11)(12). Some studies reported hemodynamic alterations and recovery time in the LMA group during general anesthesia were similar to those in the tracheal intubation group (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%